Epigenetic Regulation in the Pathogenesis of Rheumatoid Arthritis - Yang, Chao; Li, Dan; Teng, Dehong; Zhou, Yueru; Zhang, Lei; Zhong, Zhangfeng; Yang, Guan-Jun (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease. The etiology of RA remains undetermined and the pathogenesis is complex. There remains a paucity of ideal therapeutic drugs and treatment strategies. The epigenetic modifications affect and regulate the function and characteristics of genes through mechanisms, including DNA methylation, histone modification, chromosome remodeling, and RNAi, thereby exerting a significant impact on the living state of the body. Recently, the phenomenon of epigenetic modification in RA has garnered growing research interest. The application of epigenetically modified methods is the frontier field in the research of RA pathogenesis. This review highlights the research on the pathogenesis of RA based on epigenetic modification in the recent five years, thereby suggesting new methods and strategies for the diagnosis and treatment of RA.